2003
DOI: 10.1021/ol0358206
|View full text |Cite
|
Sign up to set email alerts
|

NaIO4-Mediated Selective Oxidative Halogenation of Alkenes and Aromatics Using Alkali Metal Halides

Abstract: [reaction: see text] NaIO(4) oxidizes alkali metal halides efficiently in aqueous medium to halogenate alkenes and aromatics and produce the corresponding halo derivatives in excellent regio and stereoselectivity. The system also demonstrates the asymmetric version of bromo hydroxylation using beta-cyclodextrin complexes, resulting in moderate ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(53 citation statements)
references
References 7 publications
(4 reference statements)
2
51
0
Order By: Relevance
“…[9][10][11][12][13] Consequently, there has been an interest in developing enzymes that can utilise benign inorganic halides in water to deliver haloaromatic compounds. [4][5][6][7][8][9][10][11][12][13][14][15][16] Nature has evolved halogenase enzymes for the biosynthesis of a diverse array of halogenated natural products including many antibiotics, antitumor agents and other bioactive compounds, with the halogen substituents often contributing to the biological activity of these secondary metabolites. [17][18][19][20] The Flavin-dependent halogenase (Fl-Hal) enzymes, which typically halogenate aromatic precursors, are particularly common in secondary metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] Consequently, there has been an interest in developing enzymes that can utilise benign inorganic halides in water to deliver haloaromatic compounds. [4][5][6][7][8][9][10][11][12][13][14][15][16] Nature has evolved halogenase enzymes for the biosynthesis of a diverse array of halogenated natural products including many antibiotics, antitumor agents and other bioactive compounds, with the halogen substituents often contributing to the biological activity of these secondary metabolites. [17][18][19][20] The Flavin-dependent halogenase (Fl-Hal) enzymes, which typically halogenate aromatic precursors, are particularly common in secondary metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Sodium periodate mediated bromohyroxylation of styrene-b-cyclodextrin complexes has also been reported to give low levels of enantioselectivity (22-41 % ee). [23] Another early approach is desymmetrization by chiral titanium complexes. In 26, iodolactonization in the presence of a chiral titanium complex based on TADDOL derivative 27 gave cis-28 in 65 % ee (Scheme 7).…”
Section: Asymmetric Halogenation Of Olefins: Stoichiometric Methodsmentioning
confidence: 99%
“…3 Only few reports on the asymmetric halohydrin reaction are known in literature. [4][5][6] Henry et al first reported palladium(II)-catalyzed enantioselective hydroxychlorination of terminal alkenes with a metal chloride-mechanistically it is a hydroxychlorination to alkenes and there is no involvement of halonium (X C ) intermediate. 4 Sudalai et al described NaIO 4 mediated oxidative enantioselective halohydrination of alkenes (encapsulated in b-cyclodextrin) using alkali metal halides with moderate enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…4 Sudalai et al described NaIO 4 mediated oxidative enantioselective halohydrination of alkenes (encapsulated in b-cyclodextrin) using alkali metal halides with moderate enantioselectivity. 5 Barluenga et al reported a highly diastereoselective iodohydrination of terpene derivatives using Py 2 IBF 4 . 6 There are only a few methods, other than halohydrin reaction, for the stereoselective synthesis of the a-halo-bhydroxycarboxylic acid derivatives.…”
Section: Introductionmentioning
confidence: 99%